From “ to “: An Examination of the “ Project Among Adolescents in North-Central Region of Nigeria - Taiwo O. Afolabi (SAGE Open, 2018)
This article investigates theater techniques employed in addressing self-stigmatization in Skul Konekt project, an “ anti - self - stigma ” HIV/AIDS theater intervention in Nasarawa state, Nigeria. The project toured secondary schools in Nasarawa State to create awareness on the negative effect of self-stigmatization in people living with HIV/AIDS (PLHIV). This study answers the research question: What theater techniques were employed in the Skul Konekt project and how did these strategies address the theme of self-stigmatization in PLHIV? My arguments are supported with the play text, titled, Talk to Me , and reflections from the playwright and selected actors. My reflection as a participant–observer in the project; comments from government officials, students, parents, and teachers during talkback session; and evaluation sessions from the project coordinator form part of the analysis of the impact of the theater techniques. Findings show that many intervention campaigns focus on stigmatization rather than self-stigmatization because such campaigns are designed through a top-down participatory approach without much consultation with the people. It concludes by discussing the implications of the findings for participatory strategies that can foster open communication, collaboration, and a people-led participatory approach relevant in achieving UNAIDS 90-90-90 objectives.